Operational Management Approaches/Suggestions to Strengthen the Academics of the Tribhuvan University - Choudhary, Satyanarayan (Journal of Development Review, 2020)
This article tries to analyze the existing functions of Tribhuvan University from the perspectives of its operational efficiencies for its sustaining, even not the growth, in the 21st century. Its current status has raised many questions due to current and potential student’s behavior seeking higher education from abroad. The methodology adopted is comparing its existing performance with the performances envisaged by the world-class university’s quality concept.